Prácticas culturales para el manejo de la sigatoka negra en bananos y plátanos - Orozco Romero, José; Pérez Zamora, Octavio; Manzo Sánchez, Gilberto; Farias Larios, Javier; Da Silva Moraes, Wilson; Orozco Santos, Mario (Brazilian Phytopathological Society, 2018)
Plátano-Musa sapientum